2023
DOI: 10.1002/ccd.30851
|View full text |Cite
|
Sign up to set email alerts
|

How to perform a successful drug‐coated balloon angioplasty? Tips and tricks

Sandeep Basavarajaiah,
Harkaran Kalkat,
Gurbir Bhatia
et al.

Abstract: Drug‐coated balloons (DCB) offer an excellent alternative to stents as the antiproliferative drugs are delivered via balloons and hence there is no permanent implant of metal or polymer. This rationale applies perfectly in in‐stent restenosis (ISR) as we want to avoid another layer of metal in a previously failed stent. However, their use has also been extended to de novo lesions especially in patients and lesion subsets where stents are not ideal. There is an increased desire toward expanding this further and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Therefore, the lack of a significant association in this study may suggest that the appropriateness of aggressiveness in lesion preparation before DCB implantation, supported by IVI, is crucial to ensure a thorough inspection of lesion characteristics after pre-dilatation. This was consistent with a review by Basavarajaiah et al, who recommended IVI with a modified balloon as the preferred lesion preparation choice for complex calcified lesions ( 26 ). Theoretically, the local tissue drug distribution of DCB should be superior after more pronounced neointimal modification with a scoring balloon, as observed in the RCT study by Kufner et al In that study, DCB pre-dilatation using a scoring balloon in 203 patients with ISR showed a lower rate of angiographic restenosis in the scoring balloon pre-dilatation arm compared to that via standard therapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, the lack of a significant association in this study may suggest that the appropriateness of aggressiveness in lesion preparation before DCB implantation, supported by IVI, is crucial to ensure a thorough inspection of lesion characteristics after pre-dilatation. This was consistent with a review by Basavarajaiah et al, who recommended IVI with a modified balloon as the preferred lesion preparation choice for complex calcified lesions ( 26 ). Theoretically, the local tissue drug distribution of DCB should be superior after more pronounced neointimal modification with a scoring balloon, as observed in the RCT study by Kufner et al In that study, DCB pre-dilatation using a scoring balloon in 203 patients with ISR showed a lower rate of angiographic restenosis in the scoring balloon pre-dilatation arm compared to that via standard therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, the lack of a significant association in this study may suggest that the appropriateness of aggressiveness in lesion preparation before DCB implantation, supported by IVI, is crucial to ensure a thorough inspection of lesion characteristics after pre-dilatation. This was consistent with a review by Basavarajaiah et al, who recommended IVI with a modified balloon as the preferred lesion preparation choice for complex calcified lesions (26).…”
Section: Complexity Lesion Lesion Preparation and Intravascular Imagi...supporting
confidence: 90%
“…Although this approach might be perceived as time-consuming and not widely adopted, especially in busy catheterization laboratories, the patient's benefit regarding clinical outcomes is of great value for preserving vessel vasomotricity and leaving nothing behind. 7 Last, more data are still needed on the performance of DCBs in the complex lesion setting, which is the current frontier of interventional cardiology and where the clinical research is heading.…”
mentioning
confidence: 99%